Personal Maturity and Its Reflections in Conceptual Lithuanian Education Documents - Miseliūnaitė, Brigita; Cibulskas, Gintautas (Acta Paedagogica Vilnensia, 2020)
The 2019 guidelines for the renewal of general education programs in Lithuania state that there is a lack of coherence between the goals of education, the implementation of the curriculum, and the assessment of students’ achievements. The description of Lithuanian primary, basic and secondary education (2015) states that the main result of education is the gradually acquired competencies indicating the spiritual, intellectual and physical maturity of a person, which include knowledge, understanding, abilities and attitudes. This presupposes that state maturity exams should be designed to reflect the competencies, knowledge, understanding, abilities and attitudes that indicate a person’s maturity. Based on this idea, a qualitative study was conducted in 2020. Its aim was to determine the indicators of personal maturity in Lithuanian conceptual educational documents. To achieve the research goal, we applied the data collection method (document analysis) and the data processing method (content analysis). Qualitative research has shown that a person’s maturity in Lithuania is identified based on a set of competencies. To complete their general education, students should have the following competencies: social, emotional and healthy lifestyles; cognition; creativity; civil, cultural communication. A review of the scientific literature presupposes that at the stage of late adolescent personality development, a person is yet to be in search of their identity. The documents emphasize that competencies are assessed in teacher-student interactions by accumulating qualitative evidence of competencies. Meanwhile state maturity exams measure three groups of cognitive abilities: knowledge and understanding, application of knowledge, and advanced thinking abilities. Personal values and beliefs are not reflected in state maturity exams. The conclusion of the research is that maturity exams do not reflect the maturity of a person described in the conceptual documents of Lithuanian education.